The Perception of Waiting Times on Patient Satisfaction and Patient Care: A Cross-Sectional Study at a Tertiary Health Care Institution in Kenya - Soud Seif; Jasmit Shah; Ali Chandani; Sayed K. Ali (PLoS ONE, 2025)
Introduction Patients often spend significant time waiting for care, which influences patient satisfaction, perceived quality, access to care, and utilization of various health care services. Waiting time and resulting implications remain understudied in low- and middle-income countries like Kenya. This study aimed to describe the impact on the perception of waiting times on patient satisfaction and care at a tertiary healthcare institution in Kenya. Method We conducted a prospective cross-sectional study between the first of April 2023 and the thirty-first of August 2023 at the Emergency Room (ER) at Aga Khan University Hospital, Nairobi. Data was collected through a structured questionnaire examining demographics and patient wait times. Descriptive statistics were summarized using frequencies and percentages, and univariate analyses using Fisher’s exact test were conducted for group comparisons. Results A total of 941 patients participated in the study, with 52.0% being females and 53.6% in the 20–40-year age group. More than half of the patients were married (52.4%), had a university education (75.9%), and were employed (70.6%). Of the patients who took the survey, 51.1% reported waiting for 31–60 minutes, while 25.4% reported waiting for more than 60 minutes. Most patients presented to the ER on Monday, most frequently between 0800 and 1200 hrs. Most patients (70.8%) were likely to return for care and 71.7% were likely to recommend care at the ER to relatives and friends. Conclusion Specific days and times of visits to the ER were associated with prolonged waiting times. To reduce waiting times and improve access to healthcare services, facilities should consider increasing the number of healthcare providers during these peak hours to ensure timely and quality consultations. Identifying bottlenecks and gridlocks within healthcare facilities is crucial to developing an efficient blueprint that aims to improve waiting times, leading to improved patient satisfaction and care.